Impelementasi Peraturan Daerah Istimewa Yogyakarta Nomor 1 Tahun 2014 Tentang Penanganan Gelandangan dan Pengemis Perspektif Maqasyid Al-Syari'ah - Muhammad Zainal Abidin; Inna Fauziatal Ngazizah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2022)
Regional Regulation of Special Region of Yogyakarta No. 1 of 2014 on Handling of Homeless and Beggars. This regulation outlines the implementation of handling procedures and sanctions for homeless, beggars, and givers. The objective of issuing this regulation is to reduce the number of homeless and beggars in the Special Region of Yogyakarta. The problem is regarding the criminalization of homeless and beggars as well as those who give goods or money. Therefore, this study mainly discusses the process of issuing and implementing the regulation on handling of homeless and beggars in the Special Region of Yogyakarta, and the implementation of Regional Regulation of Special Region of Yogyakarta No. 1 of 2014 seen from maqasid al-shariah perspective. This was an empirica normative legal research using a sociological-normative approach. The data were collected through interviews, documentation and observation, with an analysis using Miles Hubberman’s interactive model. The results showed that: the process of issuing the regulation on handling of homeless and beggars was done in four plenary meetings and approved by seven factions. The implementation of the regulation on handling of homeless and beggars is comprised of preventive measures, coercive measures, rehabilitation and social reintegration. In terms of maqashid al-shari’ah perspective, the regulation on handling of homeless and beggars in Yogyakarta has fitrah content, al-samahah (tolerance), al-musawah (justice), al-hurriyah (freedom).